Saluran dan Margin Pemasaran Ikan Asin di Kabupaten Fakfak - Muh Haidir Hakim; Maryati; La Andi (Tarjih : Agribusiness Development Journal, 2022)
West Papua has a large sea area and has the opportunity to develop the fisheries sector. This abundant amount of fish in Fakfak Regency must be able to be utilized. Therefore, fish can be processed so that it will provide added value, one of which is processed salted fish. The purpose of this study was to find out the marketing channels for salted fish in Dulan Pokpok Village, Fakfak Regency and to find out the margin costs of salted fish in Dulan Pokpok Village, Fakfak Regency. The method used in this study is qualitative research using descriptive methods. The results of this research show that the marketing channel in Dulan Pokpok Village consists of 4 marketing channels, namely the first marketing channel from producer to consumer, the second marketing channel for producers to buy fresh fish from fishermen then producers process into salted fish and then sell it to consumers, the third marketing channel producers buy from fishermen then sell to retailers then retailers then sell to consumers and the marketing channels of the four producers buy fresh fish from fishermen and processed into salted fish after that it is sold to collecting merchants, collecting merchants sell to retailers then retailers sell to consumers. The margin at the salted fish producer level is IDR 15,000,-/kg to IDR 20,000,-/kg, at the collection merchant level of IDR 5,000,-/kg, at the retailer merchant level of IDR 5,000,-/kg to IDR 10,000,-/kg.